Sparsity-Guided Phase Retrieval to Handle Concave- and Convex-Shaped Specimens in Inline Holography, Taking the Complexity Parameter into Account - Yao Koffi; Jocelyne M. Bosson; Marius Ipo Gnetto; Jeremie T. Zoueu (Optics)
In this work, we explore an optimization idea for the complexity guidance of a phase retrieval solution for a single acquired hologram. This method associates free-space backpropagation with the fast iterative shrinkage-thresholding algorithm (FISTA), which incorporates an improvement in the total variation (TV) to guide the complexity of the phase retrieval solution from the complex diffracted field measurement. The developed procedure can provide excellent phase reconstruction using only a single acquired hologram.